Determination of Fuel Type for Optimal Performance and Emission in a CI Engine Used Biodiesel and its Blends via Multi-Criteria Decision Making - Sinan Erdoğan; Mustafa Kemal Balki; Cenk Sayın (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, fuel type which provides optimum engine performance and exhaust emission for a compression ignition (CI) engine used alternative fuel was determined by COPRAS in multi criteria decision making (MCDM), and it was ranked from good to bad. Furthermore, the engine performance and exhaust emission results obtained from the use of fuels are discussed. In the experiments, pure biodiesel, diesel and biodiesel/diesel blend fuels at ratio of 5, 20 and 50% by volume were used as alternative fuel. The performance and exhaust emission characteristics of the engine have been obtained in the tests performed at constant load (7.2 kW) and engine speed (1500 rpm). According to experimental results, with the increase of the biodiesel ratio in the mixture fuel, it has been observed that while the specific fuel consumption is increased compared to diesel, the thermal efficiency is partially reduced. At the same time, the hydrocarbon (HC), carbon monoxide (CO) and nitrogen oxide (NOx) emissions decreased while the carbon dioxide (CO2) emission increased. According to COPRAS method, the ranking of fuels from best to worst was calculated as B5>B20>B50>B0>B100.